Tasks Of Translating Technical Material from English into Russian - Xusanova Indira Akbardjanovna; Rakhmonova Saodat Akmal kizi (Peerian Journals Publishing, 2022)
The development of such an area as the translation of scientific and technical texts occupies an important place among the urgent tasks of modern translation, due to the acceleration of the scientific and technical process, this type of translation is becoming more and more in demand. Translation of a text in a foreign language always faces many difficulties.
Keywords: literature; dictionaries; certificates of conformity of products; engineering plans